Axial Compressor Stall and Surge Prediction by Measurements - H. Hönen (International Journal of Rotating Machinery)
The paper deals with experimental investigations and analyses of unsteady pressure distributions in different axial compressors. Based on measurements in a single stage research compressor the influence of increasing aerodynamic load onto the pressure and velocity fluctuations is demonstrated. Detailed measurements in a 14-stage and a 17-stage gas turbine compressor are reported. For both compressors parameters could be found which are clearly influenced by the aerodynamic load.